Gender Equality and the COVID-19 Pandemic: Labour Market, Family Relationships and Public Policy - Paola Profeta (Intereconomics)
Abstract During the recovery, investing in gender equality is essential: it will lead directly to higher GDP and indirectly to increase human capital and promote a sustainable society. Or Women as economic agents may themselves have an impact on policies: the changing role of women in families and societies and their greater representation in decision making positions contribute to focusing and redirecting the policy agenda toward items that ultimately reduce gender gaps.